Kepatuhan Laporan Keuangan Koperasi di Kalimantan Timur pada SAK ETAP: (Compliance of Cooperative Financial Reports in East Kalimantan with SAK ETAP) - Wahyuni, Yuli; Solihin, Danna; Hariyadi, Rina Masithoh (PT Global Digital Sains Tekno, 2023)
This research aims to see how the East Kalimantan Police Mobile Brigade Unit Cooperative uses the Non-Accountable Entity Financial Accounting Standards (SAK ETAP) in preparing its 2019 financial reports. This investigation was carried out at the East Kalimantan Regional Police Mobile Brigade Unit Cooperative. The author examines the problem and uses SAK-ETAP to solve the following problems: presentation of statements of financial position, profit/loss, changes in equity, cash flow, and financial statement notes, 2019 disclosures about assets, liabilities, income, expenses, and profit/loss; measurement: historical cost and fair value. The research results show that the 2019 East Kalimantan Regional Police Mobile Brigade Cooperative financial reports and SAK ETAP meet the standards and are in accordance with the Financial Accounting Standards for Non-Accountable Entities (SAK ETAP). However, the 2018 and 2019 financial reports of the East Kalimantan Police Mobile Brigade Unit Cooperative, prepared in conformity with SAK ETAP guidelines, consist of two main components: the balance sheet, which includes six items, and the profit/loss report, which includes two items. However, there are still differences in the data. ABSTRAK: Penelitian ini bertujuan untuk melihat bagaimana Koperasi Satuan Brimob Polda Kalimantan Timur menggunakan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas (SAK ETAP) dalam penyusunan laporan keuangannya tahun 2019. Investigasi ini dilakukan di Koperasi Satuan Brimob Polda Kalimantan Timur. Penulis meneliti masalah dan menggunakan SAK-ETAP untuk menyelesaikan masalah berikut: penyajian laporan posisi keuangan, laba/rugi, perubahan ekuitas, arus kas, dan catatan laporan keuangan, pengungkapan tahun 2019 tentang aset, liabilitas, pendapatan, beban, dan laba/rugi; pengukuran: biaya historis dan nilai wajar. Hasil penelitian menunjukkan bahwa laporan keuangan Koperasi Satuan Brimob Polda Kalimantan Timur tahun 2019 dan SAK ETAP memenuhi standar dan sesuai dengan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas (SAK ETAP). Namun, laporan keuangan Koperasi Satuan Brimob Polda Kaltim tahun 2018 dan 2019 yang dibuat sesuai dengan pedoman SAK ETAP terdiri dari dua komponen utama: neraca, yang mencakup enam item, dan laporan laba/rugi, yang mencakup dua item. Namun, masih ada perbedaan dalam data.